2018
DOI: 10.2478/ata-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of Increasing the Wearing Resistance of Mulcher Tools

Abstract: This paper presents a utilization of mulcher tools, their wear and possibilities of increasing their lifetime and durability based on analysis and tests. Mulcher tools are subjected to a very strong wear causing the loss of soldered WC tips in some cases and even permanent deformation of the body tool made of steel 14 220 (16MnCr5) during the continuous use. Images depicting the loss of material from the mulcher tool due to wear were produced by overlaying the pre- and after-wear tools by means of the optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…A significant conclusion is that the strong adhesive bonding of the base, edges and other layers necessary for the safe use of the ski are in direct interaction with the slope. Interaction of the functional surface with the external environment is one of the basic requirements to ensure the functioning of the production [ 27 , 28 ]. Delamination of the base and edges was not demonstrated by SEM image analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A significant conclusion is that the strong adhesive bonding of the base, edges and other layers necessary for the safe use of the ski are in direct interaction with the slope. Interaction of the functional surface with the external environment is one of the basic requirements to ensure the functioning of the production [ 27 , 28 ]. Delamination of the base and edges was not demonstrated by SEM image analysis.…”
Section: Resultsmentioning
confidence: 99%
“…При проведении лесовосстановления и реконструкции лесонасаждений, кроме применения традиционных лесных машин (харвестеров и форвардеров, машин для транспортировки лесосечных отходов) [4,6,22] с последующим удалением пней и корней корчевателями различной конструкции [3,5,10], перспективным является применение мульчеров и ротоваторов [1,8,12], которые требуют значительных затрат мощности на их привод. В связи с этим целью исследований является изучение влияния различных природно-производственных факторов на выбор параметров технологического оборудования [15,21], базового шасси [11] и их надежность [18,20]. В настоящий момент отсутствуют методики и рекомендации, позволяющие производить расчет фрезерного оборудования для имеющегося базового шасси или решать обратную задачу, в том числе на основе математического моделирования [11,13].…”
Section: Introductionunclassified
“…Many researchers suggested conventional heat treatment processes to enhance the wear resistance and surface hardness properties of materials, working under adverse conditions as per their applications [42]. Tavodova et al [43] studied the abrasive wear resistance of quenched and tempered heat treated 16MnCr5 mulcher tools and observed that after heat treatment, the ferritic-pearlitic steel structure was converted into a tempered martensitic structure, which exhibited higher wear resistance and hardness than untreated steel. In another study, Singh et al [32] examined the wear behaviour of cryogenically treated 30MnCrB4 rotavator blades and found 60% and 260.73% enhancement in wear resistance and hardness level respectively in comparison of bare rotavator blade.…”
Section: Introductionmentioning
confidence: 99%